The study of normal pregnancy in women with hereditary thrombophilia - M. V. Khruslov (Акушерство, гинекология и репродукция, 2016)
Objective: The definition of the conditions under which women with inherited thrombophilia can have a positive pregnancy outcome. Materials and Methods. We conducted a retrospective and partially prospective analysis of 100 women with various forms of hereditary thrombophilia with the purpose of studying the conditions of a positive outcome of pregnancy. Results. We learned that normal uncomplicated pregnancy is possible if the age of the pregnant geminimen 26 years or properly selected antithrombotic therapy. Later than the time of menarche and the presence of a large number of mutations, mainly homozygous forms are markers of phenotypic manifestation of hereditary thrombophilia, starting with the first pregnancy. Conclusion. Timely diagnosis of genetic mutations and polymorphisms of thrombophilia (pre-pregnancy), pregravid proper training and appropriate management of pregnant women with the use of antiplatelet and (or) anticoagulant therapy let to get a good results by reducing the performance of reproductive losses and complications of pregnancy.